Semites, Iranians, Greeks, and Romans : studies in their interactions - Goldstein, Jonathan A., 1929- (Brown Judaic studies, 2020)
"This is a collection of several of Goldstein's previously published articles. These articles deal with two themes that have animated much of Goldstein's scholarly interests, intercultural borrowing and religious resistance to foreign rule. Jonathan Goldstein taught at the University of Iowa for 35 years and passed away in 2004"--Provided by publisher